Positive electrode active material for lithium ion secondary battery and lithium ion secondary battery
Patent Information
- Application Number
- JP2021530630
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-07-08
- Filing Date
- 2020-06-30
- Publication Date
- 2025-03-13
- Estimated Expiration
- 2040-06-30
AI Technical Summary
【0019】 本発明によれば、非常に高い熱安定性を低コストで実現できる正極活物質を提供することができる。また、本発明は、このような正極活物質を、工業規模の生産において容易に製造することが可能であり、工業的価値は極めて大きいものといえる。
Smart Images

Figure 0007645181000003 
Figure 0007645181000004 
Figure 0007645181000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a positive electrode active material for a lithium ion secondary battery and a lithium ion secondary battery. [Background technology]
[0002] In recent years, with the widespread use of portable electronic devices such as mobile phone terminals and notebook computers, there has been a strong demand for the development of small, lightweight non-aqueous electrolyte secondary batteries that have high energy density and durability. There has also been a strong demand for the development of high-output secondary batteries for use in power tools and electric vehicles, including hybrid vehicles.
[0003] As a secondary battery that meets such requirements, there are non-aqueous electrolyte secondary batteries such as lithium ion secondary batteries. Lithium ion secondary batteries that use lithium metal composite oxides having a layered or spinel type crystal structure as a positive electrode active material can obtain a high voltage of about 4V, and therefore are being put into practical use as batteries with high energy density.
[0004] Lithium metal composite oxides include lithium cobalt composite oxide (LiCoO2), which is relatively easy to synthesize, lithium nickel composite oxide (LiNiO2), which uses nickel, which is cheaper than cobalt, and lithium nickel cobalt manganese composite oxide (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2), lithium manganese composite oxide (LiMn2O4), lithium nickel manganese composite oxide (LiNi 0.5 Mn 0.5 O2) have been proposed.
[0005] However, when a non-aqueous electrolyte is used as a battery material, lithium ion secondary batteries are required to have high thermal stability. For example, when a short circuit occurs inside a lithium ion secondary battery, heat is generated due to a sudden current, so that higher thermal stability is required.
[0006] Therefore, lithium nickel cobalt manganese composite oxide and lithium nickel manganese composite oxide, which have excellent thermal stability, are attracting attention. Lithium nickel cobalt manganese composite oxide is a layered compound like lithium cobalt composite oxide and lithium nickel composite oxide, and a ternary positive electrode active material is one in which the composition ratio of nickel, cobalt, and manganese at the transition metal site is 1:1:1.
[0007] In particular, in recent years, ternary positive electrode active materials and positive electrode active materials with a high nickel ratio (Hi-Ni positive electrode material) that increase the nickel ratio of lithium nickel manganese composite oxide have been attracting attention with the aim of increasing capacity. However, the increase in battery capacity due to the nickel ratio comes with a trade-off with a decrease in thermal stability, so there is a demand for positive electrode active materials that combine high performance (high cycle characteristics, high capacity, high output) with short-circuit resistance and thermal stability as lithium-ion secondary batteries.
[0008] In order to improve thermal stability, several techniques have been proposed for adding niobium to lithium metal composite oxides. For example, Patent Document 1 discloses a compound having the general formula: Li a Ni 1-x-y-z Co x M y Nb z O b (wherein M is one or more elements selected from the group consisting of Mn, Fe, and Al, 1≦a≦1.1, 0.1≦x≦0.3, 0≦y≦0.1, 0.01≦z≦0.05, 2≦b≦2.2), a positive electrode active material for a non-aqueous secondary battery has been proposed. The composition is made up of at least one compound consisting of lithium, nickel, cobalt, the element M, niobium, and oxygen. According to Patent Document 1, the Li-Nb-O-based compound present in the vicinity of the surface or inside the particles has high thermal stability, and therefore a positive electrode active material having high thermal stability and large discharge capacity can be obtained.
[0009] In addition, Patent Document 2 discloses a compound having the general formula (1): Li d Ni 1-a-b-c Mn a M b Nbc O 2+γ (In the above general formula (1), M is at least one element selected from Co, W, Mo, V, Mg, Ca, Al, Ti, Cr, Zr, and Ta, and 0.05≦a≦0.60, 0≦b≦0.60, 0.0003≦c≦0.03, 0.95≦d≦1.20, and 0≦γ≦0.5), in which at least a portion of the niobium in the lithium nickel manganese composite oxide is dissolved in the primary particles. According to Patent Document 2, it is said that a nonaqueous secondary battery can be obtained which achieves a high level of compatibility between high energy density, excellent output characteristics, and thermal stability during short circuit due to reduced conductivity. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] JP 2002-151071 A [Patent Document 2] International Publication No. 2018 / 043669 [Patent Document 3] JP 2008-017729 A [Patent Document 4] Patent No. 4807467 [Patent Document 5] JP 2006-147499 A [Patent Document 6] JP 2007-265784 A [Patent Document 7] JP 2008-257902 A Summary of the Invention [Problem to be solved by the invention]
[0011] The positive electrode active materials described in Patent Documents 1 and 2 are described as containing niobium in a specific form to improve thermal stability, but there is a demand for further improvement in thermal stability in lithium nickel manganese composite oxides having a high nickel ratio. In addition, since niobium is expensive, there is a demand for positive electrode active materials that can achieve high thermal stability at a lower cost.
[0012] The present invention has been made in view of these circumstances, and aims to realize higher thermal stability at low cost in a positive electrode active material containing a lithium nickel manganese composite oxide having a high nickel ratio. Another aim of the present invention is to provide a method for easily producing such a positive electrode active material in industrial-scale production.
[0013] Meanwhile, in order to obtain a positive electrode active material having high battery characteristics, for example, some techniques of adding titanium to a lithium metal composite oxide have been proposed. According to Patent Documents 3 to 7, a positive electrode active material made of a lithium nickel cobalt titanium composite oxide is said to have good thermal stability and high battery capacity.
[0014] Furthermore, in the case where a short circuit occurs inside a lithium ion secondary battery, one method for suppressing a sudden current due to the short circuit is considered to be, for example, to reduce the electrical conductivity or increase the volume resistivity of the positive electrode active material in a state where it is compressed in the positive electrode, as described in the above Patent Document 2.
[0015] However, the above Patent Documents 1 to 7 do not describe at all the effects of containing niobium and titanium in combination as different elements in the lithium nickel manganese composite oxide. Furthermore, the above Patent Documents 1, 3 to 7 do not describe at all the electrical conductivity or volume resistivity of the positive electrode active material in a compressed state in the positive electrode. [Means for solving the problem]
[0016] In a first aspect of the present invention, there is provided a positive electrode active material for a lithium-ion secondary battery, which includes a lithium nickel manganese composite oxide having a hexagonal layered structure and composed of secondary particles in which a plurality of primary particles are aggregated. The metal elements constituting the lithium nickel manganese composite oxide consist of lithium (Li), nickel (Ni), manganese (Mn), cobalt (Co), titanium (Ti), niobium (Nb), and optionally zirconium (Zr). The molar ratio of the metal elements is Li:Ni:Mn:Co:Zr:Ti:Nb = a:b:c:d:e:f:g (where 0.97 ≤ a ≤ 1.10, 0.80 ≤ b ≤ 0.88, 0.04 ≤ c ≤ 0.12, 0.04 ≤ d ≤ 0.10, 0 ≤ e ≤ 0.004, 0.003 < f ≤ 0.030, 0.001 < g ≤ 0.006, and b + c + d + e + f + g = 1). In the molar ratio, (f + g) ≤ 0.030 and f > g are satisfied. Niobium is segregated at the grain boundaries between the primary particles of the lithium nickel manganese composite oxide, and the volume resistivity when compressed to 4.0 g / cm 3 is 5.0×10 2 Ω·cm or more and 1.0×10 5 Ω·cm or less. There is provided a positive electrode active material for a lithium-ion secondary battery.
[0017] Further, the molar ratio of the metal elements may be represented as Li:Ni:Mn:Co:Zr:Ti:Nb = a:b:c:d:e:f:g (where 0.97 ≤ a ≤ 1.10, 0.80 ≤ b ≤ 0.88, 0.04 ≤ c ≤ 0.12, 0.04 ≤ d ≤ 0.10, 0 ≤ e ≤ 0.004, 0.003 < f ≤ 0.030, 0.003 ≤ g ≤ 0.006, and b + c + d + e + f + g = 1). Also, it is preferable that the niobium concentration at the grain boundaries between primary particles is 1.3 times or more the niobium concentration inside the primary particles of the lithium nickel manganese composite oxide, as determined by point analysis using STEM-EDX. Further, it is preferable that the titanium concentration at the grain boundaries between primary particles is less than 1.3 times the titanium concentration inside the primary particles of the lithium nickel manganese composite oxide, as determined by point analysis using STEM-EDX. Also, it is preferable that [(D90 - D10) / Mv], which indicates the particle size variation index calculated by D90 and D10 in the particle size distribution by the laser diffraction scattering method and the volume average particle size (Mv), is 0.80 or more and 1.20 or less. Further, it is preferable that the volume average particle size Mv is 8 μm or more and 20 μm or less.
[0018] In a second aspect of the present invention, there is provided a lithium ion secondary battery including a positive electrode, a negative electrode, and a non-aqueous electrolyte, wherein the positive electrode contains the positive electrode active material for a lithium ion secondary battery described above.
Effects of the Invention
[0019] According to the present invention, it is possible to provide a positive electrode active material that can achieve extremely high thermal stability at low cost. Further, the present invention can easily manufacture such a positive electrode active material on an industrial scale, and it can be said that the industrial value is extremely large.
Brief Description of the Drawings
[0020] [Figure 1] FIG. 1 is a diagram showing an example of a method for manufacturing a positive electrode active material according to the present embodiment. [Diagram 2] FIGS. 2(A) and 2(B) are diagrams showing an example of a method for manufacturing a nickel manganese composite compound according to the present embodiment. [Diagram 3] FIG. 3 is a schematic cross-sectional view of a coin-type battery used for battery evaluation. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] Hereinafter, in relation to this embodiment, a positive electrode active material for a lithium ion secondary battery, a method for producing the same, and a lithium ion secondary battery using the positive electrode active material will be described.
[0022] 1. Positive electrode active material for lithium-ion secondary batteries The positive electrode active material for lithium ion secondary batteries according to this embodiment (hereinafter also referred to as "positive electrode active material") includes a lithium nickel manganese composite oxide having a hexagonal layered structure and composed of secondary particles formed by agglomeration of a plurality of primary particles. The metal elements constituting the lithium nickel manganese composite oxide are lithium (Li), nickel (Ni), manganese (Mn), titanium (Ti), niobium (Nb), and optionally zirconium (Zr).
[0023] Lithium ion secondary batteries, particularly when using flammable non-aqueous electrolytes as constituent materials of the lithium ion secondary batteries, require high thermal stability. In addition, in a lithium ion secondary battery, when a short circuit occurs between the positive and negative electrodes in a charged state, a current flows suddenly, generating a large amount of heat, which may cause a chain reaction in which the positive electrode active material decomposes and generates more heat. Therefore, by using a positive electrode active material having a high volume resistivity under compressed conditions in the positive electrode, a sudden increase in current caused by a short circuit can be suppressed, and thermal stability during a short circuit can be further improved.
[0024] As a result of intensive research, the inventors have found that, in the lithium nickel manganese composite oxide used for the positive electrode active material, by combining and containing a specific amount of titanium (Ti) and niobium (Nb) in a specific distribution, the positive electrode active material has a very high volume resistivity and can achieve high thermal stability by suppressing oxygen release during overcharge, and have completed the present invention. Hereinafter, the configuration of the positive electrode active material according to this embodiment will be described in detail.
[0025] [Lithium nickel manganese composite oxide] The lithium nickel manganese composite oxide contained in the positive electrode active material is composed of secondary particles in which a plurality of primary particles are aggregated. Further, the lithium nickel manganese composite oxide has a hexagonal layered structure.
[0026] The metal elements constituting the lithium nickel manganese composite oxide are composed of lithium (Li), nickel (Ni), manganese (Mn), cobalt (Co), titanium (Ti), niobium (Nb), and optionally zirconium (Zr).
[0027] The molar ratio of the metal elements constituting the lithium nickel manganese composite oxide is represented by Li:Ni:Mn:Co:Zr:Ti:Nb = a:b:c:d:e:f:g (where 0.97 ≦ a ≦ 1.10, 0.80 ≦ b ≦ 0.88, 0.04 ≦ c ≦ 0.12, 0.04 ≦ d ≦ 0.10, 0 ≦ e ≦ 0.004, 0.003 < f ≦ 0.030, 0.001 < g ≦ 0.006, b + c + d + e + f + g = 1). Further, in the above molar ratio, f representing the molar ratio of titanium (Ti) and g representing the molar ratio of niobium (Nb) satisfy the relationship of (f + g) ≦ 0.030 and f > g. Hereinafter, the composition of each metal element will be described.
[0028] (Lithium) In the above molar ratio, a representing the molar ratio of Li corresponds to the molar ratio (Li / Me) of Li and the above metal elements Me other than lithium (that is, Ni, Mn, Co, Zr, Ti, and Nb). Further, the range of a is 0.97 ≦ a ≦ 1.10, preferably 1.00 ≦ a ≦ 1.05. When the value of a is within the above range, the reaction resistance of the positive electrode decreases and the output of the battery can be improved. Further, the range of a may be 1.00 ≦ a ≦ 1.03.
[0029] (Nickel) In the above ratio of substance amounts, the range of b, which indicates the ratio of substance amount of Ni, is 0.80≦b≦0.88, preferably 0.80≦b≦0.85, and more preferably 0.81≦b≦0.84. When the value of b is within the above range, it is possible to have high battery capacity and high thermal stability. On the other hand, when the value of b is less than 0.80, the amount of redox-capable transition metal decreases, so that the battery capacity decreases. Also, when the value of b exceeds 0.88, the thermal stability may decrease.
[0030] (manganese) In the above ratio of the amount of substance, the range of c indicating the ratio of the amount of substance of Mn is 0.04≦c≦0.12, preferably 0.06≦c≦0.12, and more preferably 0.07≦c≦0.11. When the value of c is in the above range, a high battery capacity and high thermal stability can be obtained. On the other hand, when the value of c is less than 0.04, the effect of improving thermal stability may not be obtained. Also, when the value of c exceeds 0.12, the battery capacity decreases. Also, by including manganese in the above range, the firing temperature can be increased in the firing step (S20) described later, and the dispersion of titanium and the like can be promoted.
[0031] (cobalt) In the above ratio of substance amounts, the range of d indicating the ratio of substance amount of Co is 0.04≦d≦0.10, preferably 0.04≦d≦0.08, and more preferably 0.04≦d≦0.07. When the value of d is within the above range, high thermal stability and output characteristics can be obtained. On the other hand, when the value of d is less than 0.04, the improvement effect of thermal stability and output characteristics may not be obtained. In addition, when the value of d exceeds 0.10, the ratio of Ni and Mn is relatively decreased, and the battery capacity is decreased.
[0032] (zirconium) In the above ratio of the amounts of substances, the range of e indicating the ratio of the amount of Zr is 0 ≦ e ≦ 0.004, preferably 0 ≦ e ≦ 0.0038, and more preferably 0 ≦ e ≦ 0.0035. The value of e may be 0 or may exceed 0. When the value of e exceeds 0, the output characteristics and durability can be improved. On the other hand, when the value of e exceeds 0.004, the battery capacity decreases due to the relatively lower ratios of Ni and Mn.
[0033] (Titanium) In the above ratio of the amounts of substances, the range of f indicating the ratio of the amount of Ti is 0.003 < f ≦ 0.030, preferably 0.010 ≦ f ≦ 0.030, and more preferably 0.020 ≦ f ≦ 0.030. When titanium is included in the above range together with niobium, the volume resistivity of the lithium nickel manganese composite oxide during compression can be increased very significantly compared to the case where each element is included alone, and oxygen release can be suppressed when used in the positive electrode of the secondary battery, and high thermal stability can be obtained. On the other hand, when the value of f is 0.003 or less, the effect of improving thermal stability is not sufficient. Also, when the value of f exceeds 0.030, the ratios of Ni and Mn relatively decrease, the crystal structure is not stable, and cation mixing is likely to occur, so the battery capacity significantly decreases.
[0034] (Niobium) In the above ratio of the amounts of substances, the range of g indicating the ratio of the amount of Nb is 0.001 < g ≦ 0.006, more preferably 0.003 ≦ g ≦ 0.006, and may be 0.003 ≦ g ≦ 0.005. By including niobium in the above range together with titanium, even with a small content of niobium, the volume resistivity of the lithium nickel manganese composite oxide during compression can be increased very significantly, and oxygen release can be suppressed when used in the positive electrode of the secondary battery, and high thermal stability can be achieved.
[0035] Also, in the above ratio of the amounts of substances, the sum (f + g) of the ratio of the amount of titanium (f) and the ratio of the amount of niobium (g) is 0.030 or less. When f + g is within the above range, it is possible to obtain a higher battery capacity while having high thermal stability.
[0036] In the above substance amount ratio, the substance amount ratio (g) of niobium is smaller than the substance amount ratio (f) of titanium (f>g), preferably f≧2g, more preferably f≧3g, and further preferably f≧4g. Since niobium is a more expensive element than titanium, the production cost can be reduced by making the content less than that of titanium, and high thermal stability can be achieved by combining niobium with titanium.
[0037] The composition of the lithium nickel manganese composite oxide can be measured by quantitative analysis using inductively coupled plasma (ICP) emission spectrometry.
[0038] (Distribution of Niobium) Niobium (Nb) contained in the lithium nickel manganese composite oxide according to this embodiment is preferably segregated at the grain boundaries between primary particles. The segregation of niobium can be confirmed, for example, by area / line analysis of the composition of the cross section of the primary particles using energy dispersive X-ray spectroscopy (STEM-EDX) with a scanning transmission electron microscope to detect the concentration of niobium at the grain boundaries between primary particles. Note that a part of niobium may be present inside the primary particles.
[0039] Furthermore, the niobium concentration at the grain boundaries between primary particles is preferably 1.3 times or more, more preferably 1.5 times or more, of the niobium concentration inside the primary particles, as determined by STEM-EDX. The upper limit of the niobium concentration is not particularly limited, and is, for example, 5 times or less.
[0040] The niobium concentration inside the primary particles or at the grain boundaries can be confirmed by area / line / point analysis of the composition of the cross sections of multiple secondary particles using STEM-EDX measurement.
[0041] For example, the niobium concentration at the grain boundary between primary particles can be obtained by randomly selecting 20 regions (e.g., measurement regions of 130 nm × 130 nm) including the grain boundary between primary particles from the cross sections of multiple secondary particles, confirming the composition of each region by point analysis, and calculating the average value. Similarly, when measuring the niobium concentration within a primary particle, it can be obtained by randomly selecting 20 internal regions within the primary particle, confirming the composition of each region by point analysis, and calculating the average value.
[0042] (Titanium distribution) The distribution of titanium (Ti) contained in the lithium nickel manganese composite oxide according to this embodiment is not particularly limited, and may be present at least one of the inside and grain boundaries of the primary particles, or may be dissolved in the inside of the primary particles. However, from the viewpoint of improving the battery capacity of the secondary battery, it is preferable that titanium is dissolved in the inside of the primary particles. Here, the term "dissolved titanium" refers to a state in which titanium is detected in the inside of the primary particles and titanium is not concentrated at the interface of the primary particles by surface analysis of the cross section of the secondary particles using STEM-EDX, for example. It is also preferable that titanium is detected over the entire surface inside the primary particles.
[0043] For example, the titanium concentration at the grain boundaries between primary particles relative to the titanium concentration inside the primary particles, as determined by STEM-EDX, is preferably less than 1.3 times, may be 1.2 times or less, or may be 1.0 times or less. The titanium concentration at the grain boundaries between primary particles relative to the titanium concentration inside the primary particles may be 0.8 times or more and 1.2 times or less, or may be 0.9 times or more and 1.1 times or less. The titanium concentration can be measured by area analysis by STEM-EDX, as with the niobium concentration described above.
[0044] In the lithium nickel manganese composite oxide according to this embodiment, the distribution of metal elements other than the above-mentioned niobium (Nb) and titanium (Ti) is not particularly limited. However, for example, Ni, Mn, and Co are preferably detected over the entire surface inside the multiple primary particles constituting the secondary particles.
[0045] [Volume average particle size (Mv)] The volume average particle diameter (Mv) of the positive electrode active material according to the present embodiment is preferably 8 μm to 20 μm, more preferably 10 μm to 17 μm. When the volume average particle diameter Mv is in the above range, when the positive electrode active material is used in the positive electrode of a secondary battery, it is possible to achieve both high output characteristics and battery capacity and high filling property into the positive electrode.
[0046] On the other hand, if the volume average particle diameter (Mv) is less than 8 μm, high filling property into the positive electrode may not be obtained. Also, if the volume average particle diameter (Mv) is more than 20 μm, high output characteristics and battery capacity may not be obtained. The average particle diameter can be determined, for example, from the volume integrated value measured by a laser light diffraction scattering type particle size distribution meter.
[0047] [(D90-D10) / Mv] (variability index) In the positive electrode active material according to the present embodiment, the [(D90-D10) / Mv] calculated from D90 and D10 in the particle size distribution by the laser diffraction scattering method and the volume average particle size (Mv) is preferably 0.80 or more and 1.20 or less. [(D90-D10) / Mv] indicates the particle size variation index of the particles constituting the positive electrode active material. Note that D90, D10, and Mv respectively mean the particle size (D90) at 90% of the volume of the particle amount in the particle size distribution curve, the particle size (D10) at 10%, and the volume average particle size (Mv).
[0048] When the particle size distribution of the particles constituting the positive electrode active material is in a wide range, there are many fine particles whose particle size is small relative to the volume average particle size (Mv) and many coarse particles whose particle size is large relative to the average particle size. Therefore, when the variation index is in the above range, fine particles and coarse particles are mixed, the packing density is high, and the energy density per volume can be increased. Although the manufacturing method of the positive electrode active material having the above variation index is not limited, for example, it can be obtained by preparing the nickel-manganese composite compound used in the mixing step (S10) described later by a continuous crystallization method.
[0049] On the other hand, if the variation index of the positive electrode active material is less than 0.80, the volumetric energy density may decrease. The upper limit of the variation index is not particularly limited, but is, for example, about 1.20. In addition, in the firing step (S20) described later, if the firing temperature exceeds 1000°C, the particle size variation index may exceed 1.20. In this case, when the positive electrode active material is formed, the specific surface area may decrease, the resistance of the positive electrode may increase, and the battery capacity may decrease.
[0050] [4.0g / cm 3 [Volume resistivity when compressed to The positive electrode active material according to this embodiment has a powder resistivity of 4.0 g / cm 3 When compressed to 5.0×10 2 Ω cm or more 1.0×10 5 Ω cm or less, preferably 1.0×10 3 Ω cm or more 1.0×10 4 Ω cm or less, and more preferably 2.0×10 3 Ω cm or more 1.0×10 4 Ω·cm or less. When the volume resistivity of the positive electrode active material is within the above range, high thermal stability during short circuit can be obtained. Generally, the higher the conductivity of the positive electrode active material, the lower the resistance in the electrochemical reaction, and the better the active material is considered to be. However, when thermal stability during short circuit is taken into consideration, a moderately high volume resistivity can suppress the generation of a sudden current during short circuit.
[0051] The volume resistivity is, for example, 4.0 g / cm when the positive electrode active material is weighed in the range of 4.5 g to 5.5 g and formed into a cylinder with a diameter of 20 mm. 3 After pressure molding so that the resistivity satisfies the above requirement, the resistivity can be measured in a pressurized state using a four-probe resistivity test method in accordance with JIS K 7194:1994.
[0052] [Maximum oxygen generation peak temperature] The positive electrode active material according to the present embodiment preferably has a maximum oxygen generation peak temperature of 250° C. or more, more preferably 260° C. or more, during heating in an overcharged state. The upper limit of the maximum oxygen generation peak temperature during heating is not particularly limited, but is about 300° C. or less. The maximum oxygen generation peak temperature can be measured by the method described in the Examples. The maximum oxygen generation peak temperature refers to the peak temperature at which the amount of oxygen generated during heating is maximum.
[0053] [Maximum oxygen release rate] The positive electrode active material according to the present embodiment desirably has a low maximum oxygen release rate during heating in an overcharged state. The maximum oxygen release rate is preferably 60% or less, more preferably 50% or less, when the positive electrode active material produced under the same conditions except that titanium and niobium are not added and the firing temperature is adjusted according to the composition is taken as 100%. The lower limit of the maximum oxygen release rate during heating is not particularly limited, but is about 0.1% or more. The maximum oxygen release rate can be measured by the method described in the examples. The maximum oxygen release rate refers to the weight loss rate at the time when the absolute value of the value obtained by differentiating the weight loss during heating with respect to time is the largest. The firing temperature adjusted according to the composition refers to the temperature range in which the discharge capacity is highest in that composition (i.e., the temperature range in which the crystallinity is sufficiently high), and usually tends to be higher as the amount of added elements increases.
[0054] [Thermal runaway temperature] The lithium ion battery using the positive electrode active material according to this embodiment desirably has a high thermal runaway temperature in a charged state as measured by an accelerated rate calorimeter (ARC). The thermal runaway temperature is preferably +8°C or higher, more preferably +10°C or higher, based on the thermal runaway onset temperature of a positive electrode active material produced under similar conditions, except that titanium and niobium are not added and the firing temperature is adjusted according to the composition. The upper limit of the thermal runaway temperature is not particularly limited. The thermal runaway temperature can be measured by the method described in the Examples. The thermal runaway temperature refers to the temperature at which the heat generation rate exceeds 10°C / min in the ARC measurement.
[0055] 2. Manufacturing method of positive electrode active material for lithium-ion secondary batteries 1, 2(A), and 2(B) are diagrams showing an example of a method for producing a positive electrode active material for a lithium ion secondary battery according to the present embodiment (hereinafter, also referred to as a "method for producing a positive electrode active material"). The obtained positive electrode active material contains a lithium nickel manganese composite oxide composed of secondary particles formed by agglomeration of a plurality of primary particles. Furthermore, this production method makes it possible to easily obtain a positive electrode active material containing the above-mentioned lithium nickel manganese composite oxide on an industrial scale. Note that the following description is an example of the production method according to the present embodiment, and is not intended to limit the production method.
[0056] As shown in FIG. 1, the production method according to this embodiment includes at least a mixing step (S10) of mixing a nickel-manganese composite compound, a titanium compound, a niobium compound, and a lithium compound to obtain a mixture, and a firing step (S20) of firing the mixture to obtain a lithium-nickel-manganese composite oxide.
[0057] The nickel-manganese composite compound used in the mixing step (S10) may be obtained by a method including a crystallization step (S1) and / or a heat treatment step (S2), as shown in Fig. 2(A) and Fig. 2(B). Each step will be described in detail below.
[0058] [Mixing process (S10)] As shown in Fig. 1, the mixing step (S10) is a step of mixing a nickel manganese composite compound, a titanium compound, a niobium compound, and a lithium compound to obtain a mixture. If necessary, a zirconium compound is also mixed. The titanium compound, the niobium compound, the lithium compound, and if necessary, the zirconium compound can be added and mixed, for example, in the form of powder (solid phase). Each material will be described below.
[0059] (Nickel manganese complex compound) The nickel manganese composite compound used in the mixing step (S10) can be obtained by a known method. The content (composition) of metals (Ni, Mn, Co, etc.) in the nickel manganese composite compound is almost maintained in the lithium nickel manganese composite oxide particles, so the content of each metal is preferably in the same range as the content in the lithium nickel manganese composite oxide described above. The nickel manganese composite compound used in this embodiment may contain small amounts of elements other than the above-mentioned metal elements (Ni, Mn, Co, etc.), hydrogen, and oxygen within a range that does not impair the effects of the present invention.
[0060] The nickel-manganese composite compound may be a hydroxide or an oxide. For example, a method for producing a nickel-manganese composite hydroxide includes a method of neutralization and crystallization using an aqueous solution of a metal salt and an alkaline solution. In addition, the nickel-manganese composite compound may be heat-treated to remove moisture from the nickel-manganese composite compound, or a part or all of the nickel-manganese composite compound may be converted into a nickel-manganese composite oxide. These production methods can be obtained by referring to the method described in Patent Document 2, for example.
[0061] (Titanium compounds) As the titanium compound, known compounds containing titanium can be used. The titanium compounds may be used alone or in combination of two or more.
[0062] Among these, a compound containing titanium and oxygen is preferred from the viewpoints of availability and avoiding impurities from being mixed into the lithium nickel manganese composite oxide. If impurities are mixed into the lithium nickel manganese composite oxide, the thermal stability, battery capacity, and cycle characteristics of the resulting secondary battery may be reduced.
[0063] (Niobium compounds) As the niobium compound, a known compound containing niobium can be used. Among these, the niobium compound is preferably a compound containing niobium and oxygen from the viewpoint of easy availability and avoiding the inclusion of impurities in the lithium nickel manganese composite oxide. If impurities are included in the lithium nickel manganese composite oxide, the thermal stability, battery capacity, and cycle characteristics of the obtained secondary battery may be reduced.
[0064] (Lithium compounds) The lithium compound is not particularly limited, and any known compound containing lithium can be used, such as lithium carbonate, lithium hydroxide, lithium nitrate, or a mixture thereof. Among these, lithium carbonate, lithium hydroxide, or a mixture thereof is preferred from the viewpoints of being less affected by residual impurities and dissolving at the firing temperature.
[0065] (Mixing method) The method of mixing the nickel manganese composite compound, the lithium compound, the titanium compound, the niobium compound, and optionally the zirconium compound is not particularly limited, and these particles may be mixed sufficiently to the extent that the shells of these particles are not destroyed. As a mixing method, for example, a general mixer can be used, for example, a shaker mixer, a Loedige mixer, a Julia mixer, a V blender, etc. can be used. It is preferable to mix the titanium mixture sufficiently before the firing step described later. If the mixing is not sufficient, the atomic % ratio (Li / Me, which corresponds to a in the ratio of the amount of substance) of Li and the metal element Me other than Li (Me=Ni+Mn+element M+Ti+Nb in this embodiment) varies between individual particles of the positive electrode active material, and problems such as insufficient battery characteristics can occur.
[0066] The lithium compounds are mixed so that the Li / Me ratio in the mixture is 0.97 to 1.10. In other words, the Li / Me ratio in the mixture is the same as that in the resulting positive electrode active material. This is because the Li / Me ratio in the mixture in the mixing step (S10) is the same as that in the positive electrode active material, since the molar ratios of Li / Me and each metal element do not change before and after the firing step (S20).
[0067] In addition, since the contents (ratios) of niobium (Nb) and titanium (Ti) in the mixture are almost maintained in the lithium nickel manganese composite oxide, the mixed amounts of the niobium compound and the titanium compound are preferably in the same range as the contents of niobium and titanium in the above-mentioned lithium nickel manganese composite oxide.
[0068] [Firing process (S20)] The firing step (S20) is a step of firing the mixture obtained in the mixing step (S10) to obtain a lithium nickel manganese composite oxide.
[0069] When the mixture is fired, the lithium in the lithium compound diffuses into the nickel manganese composite compound, forming a lithium nickel manganese composite oxide made of particles with a polycrystalline structure. The lithium compound melts at the firing temperature and penetrates into the nickel manganese composite compound to form a lithium nickel manganese composite oxide. The lithium compound melts at the firing temperature and penetrates into the nickel manganese composite compound to form a lithium nickel manganese composite oxide. At this time, it is considered that niobium and titanium contained in the lithium mixture also penetrate into the inside of the secondary particles together with the molten lithium compound, and also penetrate into the primary particles if there are crystal grain boundaries. The firing conditions are described in detail below, but are adjusted within the range of each firing condition described below so that the battery characteristics are optimized according to the ratio of the substance amounts of the metal elements contained in the lithium nickel manganese composite oxide.
[0070] The firing atmosphere is preferably an oxidizing atmosphere, and more preferably has an oxygen concentration higher than that of the air. By using an oxidizing atmosphere, it is possible to obtain a positive electrode active material that maintains a high battery capacity while improving thermal stability and achieves both battery characteristics and thermal stability.
[0071] The firing temperature is 760°C to 1000°C in an oxidizing atmosphere, preferably 760°C to 950°C. When firing at the above temperature, the lithium compound melts, and the penetration and diffusion of titanium are promoted. In addition, the mixture contains manganese, so that the firing temperature can be increased. By increasing the firing temperature, the diffusion of titanium and niobium is promoted. Furthermore, the crystallinity of the lithium nickel manganese composite oxide is increased, and the battery capacity can be further improved.
[0072] On the other hand, if the sintering temperature is less than 760°C, lithium, titanium, and manganese are not sufficiently diffused into the nickel-manganese composite compound, and excess lithium and unreacted particles remain, or the crystal structure is not fully aligned, resulting in a problem that sufficient battery characteristics cannot be obtained. Also, if the sintering temperature exceeds 1000°C, intense sintering may occur between the particles of the formed lithium-nickel-manganese composite oxide, and abnormal grain growth may occur. If abnormal grain growth occurs, the particles after sintering become coarse, and when the positive electrode active material is formed, the packing property decreases, and the reaction resistance increases due to the disturbance of the crystal structure, resulting in a problem that the discharge capacity decreases.
[0073] The calcination time is preferably at least 3 hours, more preferably 6 hours to 24 hours. If the calcination time is less than 3 hours, the lithium nickel manganese composite oxide may not be sufficiently produced. The furnace used for calcination is not particularly limited as long as it can calcinate the mixture in an oxygen stream, but it is preferable to use an electric furnace that does not generate gas, and either a batch type or a continuous type furnace can be used.
[0074] 3. Lithium-ion secondary battery The lithium ion secondary battery (hereinafter, also referred to as "secondary battery") according to this embodiment includes a positive electrode containing the above-mentioned positive electrode active material, a negative electrode, and a non-aqueous electrolyte. The secondary battery includes, for example, a positive electrode, a negative electrode, and a non-aqueous electrolyte. The secondary battery may also include, for example, a positive electrode, a negative electrode, and a solid electrolyte. The secondary battery may be a secondary battery that charges and discharges by desorption and insertion of lithium ions, and may be, for example, a non-aqueous electrolyte secondary battery or an all-solid-state lithium secondary battery. Note that the embodiments described below are merely examples, and the secondary battery according to this embodiment may be applied to forms that have been variously modified and improved based on the embodiments described in this specification.
[0075] The secondary battery according to this embodiment can achieve high thermal stability at low cost. The positive electrode active material used in the secondary battery can be obtained by the above-mentioned industrial manufacturing method. The secondary battery is suitable as a power source for small portable electronic devices (such as notebook personal computers and mobile phone terminals) that always require high capacity. The secondary battery is also superior in not only capacity but also durability and thermal stability during overcharging, compared with batteries using conventional lithium cobalt oxide or lithium nickel oxide positive electrode active materials. Therefore, since it is possible to reduce the size and increase the capacity, it is suitable as a power source for electric vehicles that are restricted by the mounting space. The secondary battery can be used not only as a power source for electric vehicles that are driven purely by electrical energy, but also as a power source for so-called hybrid vehicles that are used in conjunction with combustion engines such as gasoline engines and diesel engines. EXAMPLES
[0076] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples. The analysis methods for metals contained in the positive electrode active material and the various evaluation methods for the positive electrode active material in the examples and comparative examples are as follows.
[0077] (1) Composition analysis: Measured by ICP emission spectrometry.
[0078] (2) Volume average particle size Mv, and particle size variation index [(D90-D10) / average volume particle size]: Measured on a volume basis using a laser diffraction scattering type particle size distribution measuring device (Microtrack HRA, manufactured by Nikkiso Co., Ltd.).
[0079] (3) Concentration of each element The positive electrode active material was processed so that cross-sectional analysis of the primary particles could be performed by S-TEM. Twenty primary particles were randomly selected from the multiple secondary particles contained in the positive electrode active material, and the composition of the inside of each primary particle cross-section and the region including the grain boundary were analyzed by EDX of the S-TEM.
[0080] (4) Volume resistivity: 4.0 g / cm2 when 5 g of positive electrode active material is put into a cylinder with a diameter of 20 mm 3 The resistivity was measured in a pressurized state using the four-probe method in accordance with JIS K 7194:1994.
[0081] (5)Initial discharge capacity: The initial charge capacity and initial discharge capacity were measured by preparing a coin-type battery CBA shown in FIG. 3 by the following method, leaving it for about 24 hours, and after the open circuit voltage OCV (open circuit voltage) had stabilized, applying a current density of 0.1 mA / cm to the positive electrode. 2 The initial charge capacity was determined by charging the battery to a cut-off voltage of 4.3 V, and after one hour of rest, the initial discharge capacity was determined by discharging the battery to a cut-off voltage of 3.0 V. A multi-channel voltage / current generator (R6741A, manufactured by Advantest Corporation) was used to measure the discharge capacity.
[0082] (Making coin-cell batteries) The obtained positive electrode active material (52.5 mg), acetylene black (15 mg), and polytetrafluoroethylene resin (PTFE) (7.5 mg) were mixed and pressed at a pressure of 100 MPa to a diameter of 11 mm and a thickness of 100 μm to prepare the positive electrode (electrode for evaluation) PE shown in FIG. 3. The prepared positive electrode PE was dried in a vacuum dryer at 120 °C for 12 hours, and then a 2032-type coin-type battery CBA was prepared using this positive electrode PE in a glove box in an Ar atmosphere with a dew point controlled at -80 °C. For the negative electrode NE, lithium (Li) metal with a diameter of 17 mm and a thickness of 1 mm was used, and for the electrolyte, a mixture of equal amounts of ethylene carbonate (EC) and diethyl carbonate (DEC) with 1M LiClO4 as the supporting electrolyte (manufactured by Toyama Pharmaceutical Co., Ltd.) was used. For the separator SE, a polyethylene porous membrane with a thickness of 25 μm was used. The coin-type battery CBA was prepared by arranging the gasket GA and wave washer WW, and assembling the positive electrode can PC and the negative electrode can NC into a coin-type battery. The measurement results of the initial charge / discharge capacity and the positive electrode resistance value of the obtained positive electrode active material are shown in Table 1.
[0083] (6) Temperature of maximum oxygen generation peak The thermal stability of the positive electrode was evaluated by quantifying the amount of oxygen released by heating the positive electrode active material in an overcharged state. A coin-type battery was prepared in the same manner as in (E) and CC-charged (constant current-constant voltage) at a rate of 0.05C up to a cutoff voltage of 4.3V. The coin battery was then disassembled, and only the positive electrode was carefully removed to avoid short-circuiting, washed with DMC (dimethyl carbonate), and dried. Approximately 2 mg of the dried positive electrode was weighed and heated from room temperature to 450°C at a heating rate of 10°C / min using a gas chromatograph mass spectrometer (GCMS, Shimadzu Corporation, QP-2010plus). Helium was used as the carrier gas. The generation behavior of oxygen (m / z=32) generated during heating was measured, and the maximum oxygen generation peak temperature was obtained.
[0084] (8) Maximum oxygen release rate The maximum oxygen release rate was calculated from the weight change caused by heating the positive electrode active material in an overcharged state. A coin-type battery was prepared in the same manner as in (E) and CC-charged (constant current-constant voltage charged) at a rate of 0.05C to a cutoff voltage of 4.3V. The coin battery was then disassembled, and only the positive electrode was carefully removed so as not to short-circuit, washed with DMC (dimethyl carbonate), and dried. Approximately 10 mg of the dried positive electrode was weighed out, and the temperature was raised from room temperature to 450°C at a heating rate of 10°C / min using a thermogravimetric analyzer (TG, manufactured by Rigaku, Thermo plus II). The measurement was performed in a nitrogen atmosphere. The weight loss during heating was differentiated, and the largest value was taken as the maximum oxygen release rate. In this embodiment, a relative value was calculated with Comparative Example 1 taken as 100%.
[0085] (9) Thermal runaway temperature In order to evaluate the safety of the battery, a battery was prepared using a negative electrode with graphite as the negative electrode active material, and an ARC (Accelerated rate calorimeter) measurement test was performed. The method for preparing the battery for the ARC measurement test is described below. 95 parts by mass of the positive electrode active material, 3 parts by mass of acetylene black as a conductive material, and 2 parts by mass of polyvinylidene fluoride as a binder were mixed. The mixture was kneaded using a kneader (TK Hibismix, manufactured by Primix Corporation) to prepare a positive electrode mixture slurry. Next, the positive electrode mixture slurry was applied to an aluminum foil with a thickness of 15 μm, and the coating was dried to form a positive electrode active material layer on the aluminum foil. This was cut into a predetermined size to form a positive electrode. The prepared positive electrode and a negative electrode with graphite as the negative electrode active material were stacked so as to face each other with a separator interposed therebetween to prepare an electrode body. Next, a non-aqueous electrolyte, which was a mixture of ethylene carbonate (EC), methyl ethyl carbonate (MEC), and dimethyl carbonate (DMC) in a volume ratio of 3:3:4, with 1.2M lithium hexafluorophosphate (LiPF6) as the supporting salt, and the electrode body were inserted into an aluminum exterior body to prepare a battery for ARC measurement. The thermal runaway temperature of the prepared battery was measured under the following conditions using an Accelerated rate calorimeter (ARC, manufactured by Thermal Hazard Technology). Measurement start temperature: 130℃ Holding temperature: 20min Heat generation detection temperature: 0.02℃ / min Temperature rise: 5℃ Battery voltage: 4.2V state of charge The temperature at which the heat generation rate exceeded 10° C. / min was determined as the thermal runaway temperature. In this embodiment, the thermal runaway temperature of Comparative Example 1 was used as the reference, and the difference from the thermal runaway temperature of Comparative Example 1 was calculated and shown as the amount of thermal runaway temperature change.
[0086] Example 1 [Mixing process] Nickel manganese cobalt composite hydroxide particles (nickel:manganese:cobalt molar ratio of 85:10:5) obtained by a known method, lithium hydroxide, titanium oxide, and niobic acid were weighed out so that the mass ratio of lithium:(nickel+manganese+cobalt):titanium:niobium was 1.01:0.973:0.022:0.005, and then thoroughly mixed using a shaker mixer (TURBULA Type T2C manufactured by Willy & Bachofen (WAB)) to obtain a lithium mixture.
[0087] [Firing process] The obtained lithium mixture was calcined by holding it in an oxygen stream at 870° C. for 10 hours, and then crushed to obtain particles of lithium nickel manganese cobalt titanium composite oxide.
[0088] [evaluation] The evaluation results of the obtained positive electrode active material are shown in Table 1. In addition, the ratio of the titanium concentration at the grain boundary between primary particles to the titanium concentration inside the primary particles in the positive electrode active material (grain boundary / intragranular) was 0.9, and no concentration of titanium was observed at the grain boundary between primary particles. In addition, in some of the examples and comparative examples, the maximum oxygen release rate and / or thermal runaway temperature were evaluated, and the evaluation results are shown in Table 2.
[0089] Example 2 A positive electrode active material was obtained and evaluated in the same manner as in Example 1, except that in the mixing step, the obtained particles of nickel manganese cobalt composite hydroxide, lithium hydroxide, titanium oxide, and niobic acid were weighed so that the substance amount ratio of lithium:(nickel + manganese + cobalt):titanium:niobium was 1.02:0.975:0.022:0.003. The manufacturing conditions and evaluation results of the positive electrode active material are shown in Table 1.
[0090] Example 3 A positive electrode active material was obtained and evaluated in the same manner as in Example 1, except that in the mixing step, the obtained particles of nickel manganese cobalt composite hydroxide, lithium hydroxide, titanium oxide, and niobic acid were weighed so that the substance amount ratio of lithium:(nickel+manganese+cobalt):zirconium:titanium:niobium was 1.01:0.972:0.025:0.003. The manufacturing conditions and evaluation results of the positive electrode active material are shown in Table 1.
[0091] Example 4 In the mixing step, the obtained nickel manganese cobalt composite hydroxide particles, lithium hydroxide, zirconium oxide, titanium oxide, and niobic acid were weighed out so that the substance amount ratio of lithium:(nickel+manganese+cobalt):zirconium:titanium:niobium was 1.03:0.970:0.003:0.022:0.005, and in the firing step, the firing temperature was 860° C., and a positive electrode active material was obtained and evaluated in the same manner as in Example 1. The production conditions and evaluation results of the positive electrode active material are shown in Tables 1 and 2.
[0092] Example 5 In the mixing step, the obtained nickel manganese cobalt composite hydroxide particles, lithium hydroxide, zirconium oxide, titanium oxide, and niobic acid were weighed out so that the substance amount ratio of lithium:(nickel+manganese+cobalt):zirconium:titanium:niobium was 1.07:0.970:0.003:0.022:0.005, and in the firing step, the firing temperature was 830° C., and a positive electrode active material was obtained and evaluated in the same manner as in Example 1. The production conditions and evaluation results of the positive electrode active material are shown in Table 1.
[0093] Example 6 A positive electrode active material was obtained and evaluated in the same manner as in Example 1, except that in the mixing step, the obtained nickel manganese cobalt composite hydroxide particles, lithium hydroxide, titanium oxide, and niobic acid were weighed so that the substance amount ratio of lithium:(nickel + manganese + cobalt):titanium:niobium was 1.00:0.973:0.022:0.005. The manufacturing conditions and evaluation results of the positive electrode active material are shown in Tables 1 and 2.
[0094] Comparative Example 1 In the mixing step, no titanium compound and no niobium compound were prepared, the obtained nickel manganese cobalt composite hydroxide particles and lithium hydroxide were weighed out so that the substance ratio of lithium:nickel:manganese:cobalt was 1.02:0.85:0.10:0.05, and in the firing step, the firing temperature was 800° C., but other than that, a positive electrode active material was obtained and evaluated in the same manner as in Example 1. The production conditions and evaluation results of the positive electrode active material are shown in Tables 1 and 2.
[0095] Comparative Example 2 In the mixing step, no titanium compound was prepared, the obtained particles of nickel manganese cobalt composite hydroxide, lithium hydroxide, and niobic acid were weighed out so that the substance amount ratio of lithium:(nickel + manganese + cobalt):niobium was 1.00:0.990:0.010, and in the firing step, the firing temperature was 850° C., but other than that, a positive electrode active material was obtained and evaluated in the same manner as in Example 1. The production conditions and evaluation results of the positive electrode active material are shown in Tables 1 and 2.
[0096] Comparative Example 3 In the mixing step, the obtained nickel manganese cobalt composite hydroxide particles, lithium hydroxide, titanium oxide, and niobic acid were weighed out so that the substance amount ratio of lithium:(nickel + manganese + cobalt):titanium:niobium was 1.01:0.977:0.022:0.001, and in the firing step, the firing temperature was 840° C., but other than that, a positive electrode active material was obtained and evaluated in the same manner as in Example 1. The production conditions and evaluation results of the positive electrode active material are shown in Table 1.
[0097] [Table 1]
[0098] [Table 2]
[0099] (Evaluation Results) As shown in Table 1, the positive electrode active material obtained in the examples had a volume resistivity of 5×10 2 It is clear that the material has a resistivity of Ω·cm or more and a maximum oxygen generation peak temperature of 250°C or more, has high thermal stability, and suppresses oxygen release during overcharge. In addition, in the positive electrode active material of the example, the ratio of the titanium concentration at the grain boundaries between primary particles to the titanium concentration inside the primary particles (grain boundary / inside grain) was 0.8 to 1.1, and no concentration of titanium was observed at the grain boundaries between primary particles.
[0100] Furthermore, as shown in Table 2, the positive electrode active material obtained in the examples had a maximum oxygen release rate of 60% or less and a thermal runaway temperature of +8° C. or more compared to Comparative Example 1, which did not contain titanium or niobium. This result also shows that the positive electrode active material of the examples suppresses oxygen release during overcharging, has a higher self-heating onset temperature, and has improved thermal stability.
[0101] On the other hand, in Comparative Example 1 where neither titanium nor niobium was added, the maximum oxygen generation peak temperature was less than 250°C, and the thermal stability was lower than that of the Examples. Similarly, in Comparative Example 2 where only titanium was added, and Comparative Example 3 where a small amount of niobium was added, the maximum oxygen generation peak temperature was less than 250°C, and the thermal stability was lower than that of the Examples. [Industrial Applicability]
[0102] In this embodiment, a positive electrode active material for a lithium ion secondary battery having high thermal stability and excellent battery characteristics can be obtained by an industrial manufacturing method. This lithium ion secondary battery is suitable as a power source for small portable electronic devices (such as notebook personal computers and mobile phone terminals) that always require high capacity.
[0103] In addition, the secondary battery using the positive electrode active material according to the present embodiment has superior thermal stability and capacity compared to a battery using a conventional lithium nickel-based oxide positive electrode active material, and is therefore suitable as a power source for electric vehicles that are limited in terms of mounting space because it can be made smaller.
[0104] In addition, a secondary battery using the positive electrode active material according to this embodiment can be used not only as a power source for an electric vehicle that is driven purely by electrical energy, but also as a power source for so-called hybrid vehicles that are used in combination with a combustion engine such as a gasoline engine or a diesel engine, or as a stationary storage battery.
[0105] The technical scope of the present invention is not limited to the aspects described in the above-mentioned embodiments. One or more of the requirements described in the above-mentioned embodiments may be omitted. The requirements described in the above-mentioned embodiments may be combined as appropriate. In addition, to the extent permitted by law, the contents of Japanese Patent Application No. 2019-127263 and all documents cited in this specification are incorporated by reference as part of the description of the present text. [Explanation of symbols]
[0106] CBA: Coin cell battery (for evaluation) PE: Positive electrode (electrode for evaluation) NE: Negative electrode SE…Separator GA…Gasket WW…Wave washer PC…Positive electrode can NC: Negative electrode can G...Void
Claims
1. A positive electrode active material for a lithium ion secondary battery, comprising a lithium nickel manganese composite oxide having a hexagonal layer structure and composed of secondary particles formed by agglomeration of a plurality of primary particles, The metal elements constituting the lithium nickel manganese composite oxide are lithium (Li), nickel (Ni), manganese (Mn), cobalt (Co), titanium (Ti), niobium (Nb), and optionally zirconium (Zr); the ratio of the amounts of substances of the metal elements is expressed as Li:Ni:Mn:Co:Zr:Ti:Nb=a:b:c:d:e:f:g (where 0.97≦a≦1.10, 0.80≦b≦0.88, 0.04≦c≦0.12, 0.04≦d≦0.10, 0≦e≦0.004, 0.003<f≦0.030, 0.001<g≦0.006, and b+c+d+e+f+g=1); The ratio of the amounts of substances satisfies (f+g)≦0.030 and f>g, Niobium is segregated at grain boundaries between primary particles of the lithium nickel manganese composite oxide, 4.0 g / cm 3 When compressed to 5.0×10 2 Ω・cm or more 1.0×10 5 Ω cm or less, Positive electrode active material for lithium-ion secondary batteries.
2. 2. The positive electrode active material for a lithium ion secondary battery according to claim 1, wherein a ratio of the amounts of substances of the metal elements is expressed as Li:Ni:Mn:Co:Zr:Ti:Nb=a:b:c:d:e:f:g, where 0.97≦a≦1.10, 0.80≦b≦0.88, 0.04≦c≦0.12, 0.04≦d≦0.10, 0≦e≦0.004, 0.003<f≦0.030, 0.003≦g≦0.006, and b+c+d+e+f+g=1.
3. 3. The positive electrode active material for lithium ion secondary batteries according to claim 1, wherein the niobium concentration at the grain boundaries between the primary particles of the lithium nickel manganese composite oxide is 1.3 times or more higher than the niobium concentration inside the primary particles of the lithium nickel manganese composite oxide, as determined by point analysis using STEM-EDX.
4. 4. The positive electrode active material for lithium ion secondary batteries according to claim 1, wherein the titanium concentration at the grain boundaries between the primary particles of the lithium nickel manganese composite oxide is less than 1.3 times the titanium concentration inside the primary particles of the lithium nickel manganese composite oxide, as determined by point analysis using STEM-EDX.
5. 5. The positive electrode active material for lithium ion secondary batteries according to claim 1, wherein [(D90-D10) / Mv], which indicates a particle size variation index calculated from D90 and D10 in a particle size distribution measured by a laser diffraction scattering method and a volume average particle size (Mv), is 0.80 or more and 1.20 or less.
6. The positive electrode active material for a lithium ion secondary battery according to any one of claims 1 to 5, wherein the volume average particle diameter Mv is 8 µm or more and 20 µm or less.
7. A lithium ion secondary battery comprising a positive electrode, a negative electrode, and a non-aqueous electrolyte, the positive electrode comprising the positive electrode active material for lithium ion secondary batteries according to any one of claims 1 to 6.
Citation Information
Patent Citations
Metal gradient doped lithium battery positive electrode material
CN105870402A
Positive electrode active material for nonaqueous system secondary battery and its manufacturing method, and nonaqueous system secondary battery using the same
JP2002151071A
Positive electrode active material for non-aqueous electrolyte secondary battery, its manufacturing method, and non-aqueous electrolyte secondary battery using this
JP2006147499A
Positive electrode active material for nonaqueous electrolyte secondary battery, its manufacturing method, and nonaqueous electrolyte secondary battery using it
JP2007265784A
Coating material for preventing adhesion of incoming agrochemical
JP2008017729A